PEMERIKSAAN BERAT BADAN DAN TINGGI BADAN RUTIN SEBAGAI UPAYA OPTIMALISASI TUMBUH KEMBANG ANAK - Lailaturohmah; Neta Ayu Andera; Ratna Mildawati (Stikes Yarsi Mataram, 2023)
In order to support the optimal growth and development of children, routine checks on a child's weight and weight are an important step in detecting potential problems or delays in a child's growth from an early age. This community service activity involved 20 participants consisting of students at TPA Al-Amiin aged 4-5 years. The objective of this activity is to conduct regular weight and height check-ups for the students at TPA Al-Amiin to monitor their growth and development.The community service method is carried out by providing routine weight and height check facilities every month at the Al-Amiin TPA. The participants were encouraged to take regular check-ups to monitor the growth of the children. In addition, an educative approach is also carried out through counseling to parents regarding the importance of examining growth and development and its benefits for children's development.The results of this community service show an increase in parental participation in routine checks on child growth and development at the Al-Amiin TPA. The number of participants in May was 20 children with the result that 18 children (90%) were in the normal growth and development category. With regular check-ups, potential problems or developmental delays in children can be detected earlier, so that appropriate interventions can be given to support optimal child development.In conclusion, routine checks on child growth and development at TPA Al-Amiin through community service can provide significant benefits in optimizing children's growth and development. With increased parental participation in examinations, children's development can be monitored regularly and interventions can be made early. These steps can serve as a model for similar institutions in increasing parental participation and optimizing the growth and development of children as a whole.